1999
DOI: 10.1016/s0895-7061(99)00009-6
|View full text |Cite
|
Sign up to set email alerts
|

Sustained antihypertensive actions of a dual angiotensin-converting enzyme neutral endopeptidase inhibitor, sampatrilat, in black hypertensive subjects

Abstract: Our objective was to evaluate the safety and antihypertensive efficacy of sampatrilat, a novel dual inhibitor of both angiotensin-converting enzyme (ACE) and neutral endopeptidase (NEP), in subjects poorly responsive to ACE inhibitor monotherapy. The ability of sampatrilat (50 to 100 mg daily) (n ‫؍‬ ‫؍‬ 28) to lower blood pressure was compared with that of the ACE inhibitor lisinopril (10 to 20 mg daily) (n ‫؍‬ ‫؍‬ 30) using a double-blind, randomized, parallel group study design over a 56-day treatment perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 20 publications
1
31
0
Order By: Relevance
“…A study performed in 58 black hypertensive subjects, who are known to be poorly responsive to ACE monotherapy, confirmed these results. 37 …”
Section: Corti Et Al Vasopeptidase Inhibitorsmentioning
confidence: 99%
“…A study performed in 58 black hypertensive subjects, who are known to be poorly responsive to ACE monotherapy, confirmed these results. 37 …”
Section: Corti Et Al Vasopeptidase Inhibitorsmentioning
confidence: 99%
“…The VPI sampatrilat produced a sustained antihypertensive activity in black hypertensive patients, a patient population with a high prevalence of salt sensitivity. 17 Omapatrilat has similar inhibition constants for both NEP and ACE and is effective in low-, normal-, and high-renin models of hypertension. 18 Clinical efficacy appears to be independent of age 19 and ethnicity and may be independent of renin and salt status.…”
mentioning
confidence: 96%
“…At the end of the placebo run-in period, patients were randomized to either GW665011X or placebo (1:1 ratio) treatment in a double-blind manner. Patients in the active treatment group received two consecutive 3-day dose titration periods of GW660511X 50 mg once daily (days 1-3) and then 100 mg once daily (days 4-6) followed by GW660511X 200 mg once daily for 14 days (days [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Patients in the placebo treatment group received the same dosing regimen with a matched placebo.…”
Section: Methodsmentioning
confidence: 99%
“…7,8 Clinical evidence thus far has shown that omapatrilat, sampatrilat and fasidotril are effective in the management of hypertension in different patient populations. [9][10][11][12][13][14] However, adverse events (AE) associated with omapatrilat, especially angioedema, raised a concern for the safety of vasopeptidase inhibitors. 15 GW660511X is a novel potent and selective dual inhibitor of ACE (IC 50 3.2 nM) and NEP (IC 50 1.8 nM) both in vitro and ex vivo.…”
Section: Introductionmentioning
confidence: 99%